Analysis of Financial Feasibility of Bean Cake Business (Case Study: Jaya Bean Cake Business) Gampong Simpang Lhee, Langsa Barat District, Langsa City - Rozalina, Rozalina; Muhammad Zain Basriwijaya, Kiagus; Sarimaryoni , Hamdi; Rahmawati, Rahmawati (Edu Sosial, 2025)
This research aims to analyze the financial feasibility of the peanut cake business (Case Study: Jaya Kacang Cake Business) in Gampong Simpang Lhee, West Langsa District. The data collection methods used are primary data and secondary data. The respondent in this research is Mrs. Marliah as the owner and manager of the Kue Kacang Jaya business. The analysis calculated in this research is Production Costs, Income, Receipts, Net Present Value (NPV), Internal Return (IRR), Payback Period (PP), Profitability Index (PI). The results obtained from this research are as follows: The Net Present Value (NPV) obtained was IDR greater than zero. The Internal Of Return (IRR) obtained was 61.69% greater than the specified interest rate. The Profitability Index (PI) obtained was 1,10, greater than 1(one). The payback period (PP) obtained is 1 year 53 days. So it can be concluded that Mrs. Marliah's Jaya Kacang Cake business is worth running.